Theoretical optical absorption and electron energy loss spectroscopy using LCAO-TDDFT-K-Ω of chlorophyll and carbon nanotubes - Preciado Rivas, María Rosa (2019)
The development of more efficient, environmentally friendly, and inexpensive organic photo- voltaics (OPVs) is a fundamental challenge in nanotechnology. One promising way to address this problem is the computational design of next generation OPVs. Understanding the excita- tion processes undergone by the large molecules in such systems requires the development of novel accurate and highly efficient computational methods for describing their optical absorption spectra. In this work, we use an efficient linear combination of atomic orbitals (LCAO) repre- sentation of the Kohn-Sham (KS) wavefunctions to perform time-dependent density functional theory (TDDFT) calculations in the frequency domain using the LCAO-TDDFT-k-ω code. By applying the derivative discontinuity correction of the Gritsenko-Leeuwen-Lenthe-Baerends solid and correlation (GLLB-SC) functional to the KS eigenenergies, we obtain a semi-quantitative description of the electronic structure. In this way we can rely on these methods to obtain an accurate description of the optical absorption spectra with a significant reduction in computa- tional effort. We apply this method to calculate the optical absorption spectra of molecules such as chlorophyll monomers and dimers, single-walled carbon nanotubes and combinations thereof which are potential OPVs.